1996
DOI: 10.1111/j.1745-4530.1996.tb00387.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT of SCREW CONFIGURATION and SPEED ON RTD and EXPANSION of RICE EXTRUDATE

Abstract: The influence of screw configuration and screw speed on the residence time distribution and product expansion was determined for rice meal processed in a corotating twin screw extruder. Screw speed had strong effect on the E(t)-and F(t)-diagrams, with the mean residence time varying inversely with screw speed from 206 s to 256 s. the F-diagram was modeled by the combination of perfect mixing and plug flow. the P estimates, which express the fraction of material in plug flow, varied inversely with screw speed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…However, the effect on variance was not quiet clear. Davidson, Paton, Diosady, and Spratt (1983), Lee and McCarthy (1996), Todd (1975), and Yeh et al (1991) had reported similar results. Increased screw speed may have resulted in more viscous heat dissipation, greater pumping force and more shearing, which enabled shorter MRT and better mixing of the material.…”
Section: Effects Of Screw Speedsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the effect on variance was not quiet clear. Davidson, Paton, Diosady, and Spratt (1983), Lee and McCarthy (1996), Todd (1975), and Yeh et al (1991) had reported similar results. Increased screw speed may have resulted in more viscous heat dissipation, greater pumping force and more shearing, which enabled shorter MRT and better mixing of the material.…”
Section: Effects Of Screw Speedsupporting
confidence: 81%
“…Care was taken to make sure that the extrudates were straight after exiting the die nozzle to avoid complexity during the images processing. The a * value (of L * a * b * color space) was used as measure of concentration of tracer in the extrudate (Gogoi & Yam, 1994;Lee & McCarthy, 1996).…”
Section: Determination Of Rtdmentioning
confidence: 99%
“…Altomare and Ghossi (1986) gave a similar result for a ZSK-57 corotating twin screw extruder using rice flour. Choudhury andGuatam (1998), De Ruyck (1997), Gasner, Bigio, and Marks (1999), Gogoi and Yam (1994), , Picot (1999), Jager, van Zuilichem, Stolp, andvanÕt Riet (1988), Lee and McCarthy (1996), , and Unlu and Faller (2002) all reported the same result of decreasing mean residence time with increasing screw speed. Even though all these studies were in agreement in the inverse relationship between the mean residence time and screw speed, some of them were in conflict in terms of degree of effect of the screw speed on the mean residence time and residence time distributions compared to that of the feed rate.…”
Section: Parameter Level Relative Effects On Mean Residence Time (%)supporting
confidence: 55%
“…Several studies on the use of extrusion processing to inactivate microbial populations in food ingredients have been reported [7][8][9][10][11][12]. Likimani et al [13] proposed a methodology for determining the destruction of bacterial spores in a Brabender single-screw Plastic order extruder at different processing conditions.…”
Section: Introductionmentioning
confidence: 99%